STUDIES ON PADDY-CUM-FISH CULTURE UNDER DIFFERENT LAND SITUATIONS - KONAR, D.; GHOSH, S. H.; KUNDU, A. L.; BAIRAGYA, C. N.; DATTA, S. K. (Journal of Indian Fisheries Association, 2015)
Paddy fields can be broadly classified on the basis of land situations viz. Upland - Shallow water (10-30 em), Medium land-medium deepwater (30-100 em) and Low land-deepwater (above 100 em). Three major systems of paddy-cum-fish culture, viz. (A) high yielding paddy varieties (H.Y.V) and air-breathing fish under Upland, (B) H.Y.V. /local paddy and Tilapia/ common carp under Medium land and (C) deepwater paddy and major Indian carps under Low land situations have been successfully investigated in the farmers’ fields and at the Research Stations (1982-92). Effects of low-cost artificial feeding on growth, yield and management practices of different types of fish showed a considerable increase of rice and fish yields and a decrease in insect-pest incidence. Under Upland situation, short. duration H.Y.V. in combination with fast-growing airbreathing fish were studied thrice a year (summer, winter & autumn seasons). Combined rice and fish culture produced highest yields in all the seasons than in the control.